Nutrition and preparation of blenderized tube feeding in children and adolescents with neurological impairment: A scoping review. (11th April 2022) - Brekke, Ghita; Raun, Anne Mette Terp; Sørensen, Sarah B.; Kok, Karin; Sørensen, Jette L.; Born, Alfred P.; Mølgaard, Christian; Hoei‐Hansen, Christina E.
Abstract: Background: The use of homemade tube feeding formula has become increasingly popular for children requiring enteral nutrition. This project aimed to investigate nutrition and preparation of blenderized tube feeding in the field of children and adolescents with neurological impairment. Methods: A scoping review was performed using established methodologies. In January 2021, we searched PubMed, Embase, CINAHL Complete, the Cochrane Central Register of Controlled Trials, and gray literature to identify relevant articles. Major findings: Twenty‐two papers were included describing the composition of food items, preparation procedures, and food safety. No randomized controlled trials and only a few prospective studies were included. A broad variety of food items from all food groups and many examples of recipes were presented. Most recipes provided 1.0 kcal/ml but tended to contain less energy and nutrients than expected, which could be due to preparation issues, such as sieving and the high viscosity of the blend. Preparation requires a commercial‐grade household blender and diligence to ensure thorough household hygiene for adequate food safety. Conclusions: This review revealed practical experience in the nutrition and preparation aspects of blenderized tube feeding but minimal empirical evidence. Multiple examples of the composition of food items and preparation procedures for blenderized tube feeding were found, but uncertainty regarding the ideal composition or preparation was also exposed. The future of blenderized tube feeding would benefit from clinically tested recipes that include an evaluation of nutrients, viscosity, and microbial contamination, as well as the effect of the food's appearance and scent on the target group.